Introduction To Hijaiyah Letters Through Tilawati Method To Students Aged 5-6 - Hunainah, Hunainah; Imroatun, Imroatun; Riswanto, Dody; Hayati, Hayati (Universitas Negeri Semarang, 2021)
The research objective is to describe the introduction of Hijaiyah letters through the Tilawati method; Supporting and inhibiting factors in the introduction of Hijaiyah letters through the Tilawati method for students aged 5-6 years at the Rumah Qur'an Al-Qadr, Serang city. This research approach is descriptive qualitative, the research subjects are institution managers, teachers, students, and student guardians. Data collection techniques are using observation, interviews, documentation, and triangulation. Data are analyzed through reduction, data presentation, and verification. The results of the study (1) the introduction of hijaiyah letters in the Rumah Qur'an Al-Qadr is in accordance with the learning steps contained in the Tilawati method learning guide using the following techniques: teacher reading-students listening; teacher reading-students imitating; teacher and students both reading; and individually reading and listening using tilawati books; (2) Supporting factors: all the teachers prayed tilawati; complete media; conducive learning environment; high morale of students and teachers; the right curriculum; establishing teacher and parent communication. As for the inhibiting factor: there are still some parents who don't care; some students rarely join the class of learning Qur'an or arrive lately; the student is too tired of doing activities outside; change of teachers in the middle of the semester; inadequate vehicle parking.